The difference in accommodative amplitude and facility between the dominant and non-dominant eyes - Altoaimi, Basal Hamad (Journal of the Pakistan Medical Association, 2024)
The cross-sectional study was planned to compare the amplitude of accommodation and accommodative facility between the dominant and non-dominant eyes in young university students. The sample comprised 70 healthy young adult students at King Saud University, Saudi Arabia, who were aged 19-27 years with a mean of 21.46±1.54 years. The dominant eye for each subject was determined using the hole-in-a-card test. The push-up method and ±2.00 diopter flipper lenses were used to measure the amplitude of accommodation and accommodative facility, respectively. The mean amplitude of accommodation and accommodative facility of the dominant eye were 8.56±2.15 diopter, and 9.76±2.84 cycle/min, respectively. The corresponding figures for the non-dominant eye were 8.26±2.24 diopter, and 9.21±2.79 cycle/min. The mean difference in the amplitude of accommodation and the accommodative facility was 0.30±0.80 diopter and 0.54±1.61 cycle/min higher in the dominant eye. However, despite the statistically significant difference between dominant and non-dominant eyes in terms of the amplitude of accommodation and accommodative facility, these differences might not reach clinical relevance. Key Words: Accommodation, Eye dominance, Ocular dominance.